2008
DOI: 10.5194/acp-8-7115-2008
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of aerosol optical properties over Europe with a 3-D size-resolved aerosol model: comparisons with AERONET data

Abstract: Abstract. This paper aims at presenting a model-to-data comparison of the Aerosol Optical Thickness (AOT) and of a few sparse data for Single Scattering Albedo (SSA) over Europe for one year. The main contribution of this paper is the sensitivity study to a large number of parameters, including physical and numerical parameters of the aerosol model itself. The optical parameters are computed from a sizeresolved aerosol model embedded in the POLYPHEMUS system. The methodology is first described, showing that se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 73 publications
(63 reference statements)
3
39
0
Order By: Relevance
“…Jeong and Sokolik (2007) also showed that the way optical properties are computed (internal mixing, external mixing, core shell) do not play a strong role unless black carbon fraction is very high. This was also observed by Tombette et al (2008). We show that if the same updated cross-sections and quantum yields are used in two photolysis scheme, differences in photolysis rates are small.…”
Section: Comparisons To Previous Studiessupporting
confidence: 78%
See 2 more Smart Citations
“…Jeong and Sokolik (2007) also showed that the way optical properties are computed (internal mixing, external mixing, core shell) do not play a strong role unless black carbon fraction is very high. This was also observed by Tombette et al (2008). We show that if the same updated cross-sections and quantum yields are used in two photolysis scheme, differences in photolysis rates are small.…”
Section: Comparisons To Previous Studiessupporting
confidence: 78%
“…To translate aerosol concentrations in OD and OP the method used by Tombette et al (2008) is used: given the particle refractive index and its wet diameter, a tabulation based on a Mie code provide the OP. The Mie model developed by Mishchenko et al (1999) is used here because it calculates the 8 first terms of the Legendre expansion of the phase function (see Sect.…”
Section: On-line Treatment Of the Solar Radiation Alteration By Aerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…the AErosol RObotic NETwork -AERONET) have greatly enhanced our ability to evaluate such models. Comparisons between observed and simulated aerosol optical depth (AOD) have been performed for global models and regional models (Kinne et al, 2006;Tombette et al, 2008;Péré et al, 2010). However, instruments such as sun photometers can only retrieve columnintegrated aerosol properties and can only work during daytime.…”
Section: Y Wang Et Al: Comparison Of Lidar Observations With Aerosomentioning
confidence: 99%
“…POLAIR3D/SIREAM has been used for several applications. For example, it was compared to in situ surface measurements for gas and aerosols over Europe by Sartelet et al (2007Sartelet et al ( , 2012 and Couvidat et al (2012), and over Greater Paris by Couvidat et al (2013); it was compared to AERONET data over Europe by Tombette et al (2008) and to satellite data by Zhang et al (2013); and it was compared to lidar-derived PM 10 over Greater Paris during MEGAPOLI by Royer et al (2011).…”
Section: Polair3d Modelmentioning
confidence: 99%